2020
DOI: 10.3866/pku.whxb202008030
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Electron Transfer Realized over NiS<sub>2</sub>/MoSe<sub>2</sub> S-Scheme Heterojunction in Photocatalytic Hydrogen Evolution

Abstract: S-scheme heterojunction is a major breakthrough in the field of photocatalysis. In this study, NiS2 and MoSe2 were prepared by a typical solvothermal method, and compounded by an in situ growth method to construct an S-scheme heterojunction. The obtained composite showed excellent performance in photocatalytic hydrogen evolution; the hydrogen production rate was approximately 7 mmol•h −1 •g −1 , which was 2.05 times and 2.44 times those of pure NiS2 and MoSe2, respectively. Through a series of characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 52 publications
0
58
0
Order By: Relevance
“…8c to explore the mechanism of enhanced photocatalytic activity. As can be observed that the three samples appear increased cathode current, the MCCA-3 composite photocatalyst exhibits the smallest cathodic current response, which may be attribute to the fast electron transfer at the interface of Mn0.2Cd0.8S and CoAl LDH 55,56 . The result indicating that the MCCA-3 S-scheme heterojunction possesses superior photocatalytic hydrogen production performance than original Mn0.2Cd0.8S and CoAl LDH.…”
Section: Electrochemical Characterizationmentioning
confidence: 93%
“…8c to explore the mechanism of enhanced photocatalytic activity. As can be observed that the three samples appear increased cathode current, the MCCA-3 composite photocatalyst exhibits the smallest cathodic current response, which may be attribute to the fast electron transfer at the interface of Mn0.2Cd0.8S and CoAl LDH 55,56 . The result indicating that the MCCA-3 S-scheme heterojunction possesses superior photocatalytic hydrogen production performance than original Mn0.2Cd0.8S and CoAl LDH.…”
Section: Electrochemical Characterizationmentioning
confidence: 93%
“…According to the experimental results and the above analysis, the possible S-scheme mechanism of the H2 production process is proposed from the perspective of energy band theory and is shown in Fig. 11 [56][57][58][59][60] . As shown in Fig.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…These materials not only retain the original excellent structural properties of MOF materials but also have strong catalytic activity. 29,30 Particularly, materials formed by using imidazole salt zeolite framework material (ZIF) as the precursor to adsorb metals and metal clusters not only inherit the characteristics of large specific surface area but also show unique performance advantages in terms of high stability and controllable structure. [31][32][33] Among them, the imidazole acid zeolite skeleton ZIF-67 formed by the adsorption of cobalt-based metal clusters by the ZIF material is a 3D polyhedron with high crystallinity, large specific surface area, and uniform central ion distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the industry has derived in situ from the precursors of MOF materials, such as metal oxides, metal sulfides, and metal nitride materials. These materials not only retain the original excellent structural properties of MOF materials but also have strong catalytic activity 29,30 . Particularly, materials formed by using imidazole salt zeolite framework material (ZIF) as the precursor to adsorb metals and metal clusters not only inherit the characteristics of large specific surface area but also show unique performance advantages in terms of high stability and controllable structure 31‐33 .…”
Section: Introductionmentioning
confidence: 99%